MULTIPLIER EFFECTS OF LATVIAN RURAL DEVELOPMENT PROGRAMME 2007-2013 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The core question to be answered in periodic evaluations of EU Member States Rural Development Programme (RDP) specific policy interventions is whether the stated objectives are accomplished by particular intervention (support or „treatment” provided to programme participants). Programme effects should normally be expressed in “net” terms, which means after subtracting the effects that cannot be attributed to the intervention, and by taking into account indirect effects (deadweight, leverage, displacement, substitution and multipliers). The level of the estimation of indirect effects (micro or macro level) depends on the size of the interventions and country specific issues. In the ex-post evaluation of the Latvian Rural Development programme 2007-2013, deadweight effects, leverage effects and multipliers are estimated at the individual measure (micro) level, while substitution and displacement effects are aggregated over the sets of measures. Multiplier effect is a secondary effect resulting from increased income and consumption generated by the public intervention. Multiplier effects are cumulative and take into account the fact that a part of the income generated is spent again and generates other income, and so on in several successive cycles. In each cycle, the multiplier effect diminishes due to purchases outside the territory. The existing study provides an assessment of the multiplier coefficients (multipliers) for the economic growth in terms of Gross Value Added and for the employment creation in terms of Annual Working Units. The research results show that total estimated programme secondary cumulative impacts on economic growth and employment over the entire economy are significant and positive.